Design and Development of Credit Scoring Model for Conventional Banks for Individual Borrowing Case Study on PT BPR Sungai Puar District Agam - Rio Hendriadi; Anne Putri; Dona Amelia; Rany Syafrina (Journal of Accounting Research, Organization and Economics, 2018)
Objective – This research is conducted to design and to develop credit scoring model on conventional bank in order to determine individual loan, the research takes place in PT BPR Sungai Puar, Kabupaten Agam. This model tries to evaluate the credit risk of BPR Sungai Puar.Design/methodology – The data are considered as secondary sources as they are taken from BPR Sungai Puar database by classifying them into two analysis tools including discriminant analysis and logistic regression. Results – The resuts are presentes inform of model and credit scoring perfection on PT BPR Sungai Puar Kabupaten Agam.Keywords Credit Scoring Model, Conventional Banks, Individual Loan